An interdisciplinary modelling framework for selecting adaptation measures at the river basin scale in a global change scenario. (July 2015) - Girard, Corentin; Rinaudo, Jean-Daniel; Pulido-Velazquez, Manuel; Caballero, Yvan
Abstract: Shaping global change adaptation strategy in water resource systems requires an interdisciplinary approach to deal with the multiple dimensions of the problem. The modelling framework presented integrates climate, economic, agronomic and hydrological scenarios to design a programme of adaptation measures at the river basin scale. Future demand scenarios, combined with a down-scaled climate scenario, provide the basis to estimate the demand and water resources in 2030. A least-cost river basin optimisation model is then applied to select adaptation measures ensuring that environmental and supply management goals are achieved. In the Orb river basin (France), the least-cost portfolio selected suggests mixing demand and supply side measures to adapt to global change. Trade-offs among the cost of the programme of measures, the deficit in agricultural water supply and the level of environmental flows are investigated. The challenges to implement such interdisciplinary approaches in the definition of adaptation strategies are finally discussed. Highlights: An interdisciplinary modelling framework is presented to analyse the effects of global change on water resource systems at the basin scale. Present and future urban and agricultural water demands, as well as a climate change scenario, are integrated into a river basin management model. Future supply and demand management measures are selected using least-cost optimisation. Trade-offs between the cost of adaptation measures, irrigated agriculture development, and environmental requirements are quantified. Insights to improved integrated water management at basin scale through interdisciplinary modelling are provided.